Event Marketing Strategy During The Pandemic Crisis: Case Study Of The Westin Resort And Spa Ubud-Bali - Lukitasari, Rimalinda; Dewi, Ni Kadek Ayu Listia; Lumanauw, Nelsye (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2023)
The meeting, incentive, conference, and exhibition (MICE) activities have been one of the leading sub-sectors in Indonesian tourism, especially Bali. However, the Covid-19 pandemic has brought a massive impact on the sector. As one of the providers of MICE service in the Ubud area, The Westin Resort and Spa Ubud – Bali experienced difficulties in marketing their event service product during the pandemic, which contributed to the decrease in revenue in the hotel. This research aims to develop a marketing strategy for event service products to respond to the market conditions. This research took the qualitative approach with the data collection through observation, interviews, and documentaries. The strategy development was first started with the identification of the marketing mix components of The Westin Resort and Spa Ubud – Bali which are, product, price, place, promotion, people, process, and physical evidence. The collected data is then used in the SWOT analysis to develop the strategy for event service marketing in a pandemic situation. Based on the analysis on the internal and external factors that influence the strategy of event marketing at The Westin Resort and Spa Ubud – Bali, it was concluded that the strategies that needed to be taken were developing promotion strategies for MICE events, wellness events, meetings -stay and tour package, and entertainment show, arranging service products in the form of programs that can reduce the concerns and stress that may occur due to new normal adjustment, focusing on the small-medium exclusive events, as well as offering a more competitive price. The implications of this research are expected to contribute to the development of tourism marketing field of study, particularly the MICE, and be able to be one of the references for hoteliers developing along with the event organizer when event marketing strategy, especially in crisis conditions such as the pandemic.